Annual Plan 1981-82 Punjab - Planning Commission (Planning Commission, 1981)
The year 1981-82 represents the second year of the Sixth Five-Year Plan 1980—85. The overall strategy and objectives of the Annual Plan 1981-82 have been derived from the Sixth Five-Year Plan 1980—85—Framework, keeping in view the 20 point economic Programme, the guidelines received from the Planning Commission and the priorities of the Government. It has been formulated with a view to speeding up productive impulses in the economy and alleviating the hardships of people by providing for their day to day consumption requirements.
Planning Department Punjab